2020
DOI: 10.1149/1945-7111/ab6826
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Mechanism Behind Transition-Metal Dissolution from Delithiated LiNixMnyCozO2 (NMC) Cathodes

Abstract: Dissolution of transition metals (TMs) from lithium-ion battery cathodes under high-voltage conditions is a major issue affecting battery performance that is not well understood mechanistically. Here, this phenomenon is studied by chemically aging pristine and charged LiNi 0.5 Mn 0.3 Co 0.2 O 2 (NMC532) cathodes in the presence of different solutions. The solution composition was varied by 1) adding water to a standard electrolyte, 2) replacing LiPF 6 salt with lithium acetylacetonate (Li-acac), 3) and/or addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 45 publications
3
52
0
Order By: Relevance
“…However, our leaching results are in line with a recent report about the compatibility of Ni-rich NMC materials with a saturated LiNO 3 aqueous electrolyte that identified Ni to be the most soluble species . The apparent discrepancy between organic and aqueous electrolytes is consistent with a report on the leaching behavior of NMC532 that showed that the nature of the electrolyte affects the ratio of dissolved transition metal ions . Further studies are needed to better understand the preference for Ni dissolution in WIS electrolytes.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…However, our leaching results are in line with a recent report about the compatibility of Ni-rich NMC materials with a saturated LiNO 3 aqueous electrolyte that identified Ni to be the most soluble species . The apparent discrepancy between organic and aqueous electrolytes is consistent with a report on the leaching behavior of NMC532 that showed that the nature of the electrolyte affects the ratio of dissolved transition metal ions . Further studies are needed to better understand the preference for Ni dissolution in WIS electrolytes.…”
Section: Resultssupporting
confidence: 89%
“…30 The apparent discrepancy between organic and aqueous electrolytes is consistent with a report on the leaching behavior of NMC532 that showed that the nature of the electrolyte affects the ratio of dissolved transition metal ions. 31 Further studies are needed to better understand the preference for Ni dissolution in WIS electrolytes.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Besides loss of Li, ICP-MS data in Figure 6 maps out the extent of transition metals (TM) (e.g., Ni, Co, Mn) that migrated from NMC811 to the anode for different XFC conditions at different cycles. TM dissolution in NMC chemistry has been reported to happen predominantly at a higher voltage (e.g., >4.3 V) [44][45][46] contributing to capacity fade and impedance rise. Here, the primary goal was to investigate whether different XFC conditions (e.g., 1C to 9C) with lower charge voltage (e.g., ≤4.1 V) would lead to any distinctly different TM dissolution, and if so, how that would affect the electrochemical data.…”
Section: Icp-ms Of Dissolved Metalsmentioning
confidence: 99%
“…Transition metal dissolution in the NMC chemistry has been reported to occur predominantly at a higher voltage (>4.3 V) for the non‐XFC conditions. [ 143–145 ] Bulk measurement of TM dissolution through ICP‐MS remains mostly comparable for the charging rates between the 1C to the 9C with a 4.1 V charge cutoff for both the NMC532 and NMC811 cathodes. Similar to non‐XFC and higher voltage conditions, [ 143,144 ] the NMC532 cells had more Mn dissolution, while the NMC811 cells had a higher Ni dissolution than the other two metals.…”
Section: Cathode Cycle‐life Performance Under Xfcmentioning
confidence: 95%